Drama-Based Mathematics Learning Model For Character Building Of Students In Elementary School - Ramlan Ramlan (Jurnal Indonesia Sosial Teknologi, 2023)
Facing the problem of the Indonesian nation which is being hit by a 'moral crisis', the concept of the national education curriculum contains a lot of character education concepts. This is a new challenge so that teachers immediately change the 'mindset' that originally the purpose of teaching to produce intelligent humans, to having to prioritize teaching to form character. Mathematical characteristics are abstract sciences, but the process of understanding must be conveyed through concrete media. In addition, the psychological development of elementary school children is in the urge to want to play and do fun activities. This research aims to get findings of mathematics learning models in elementary schools to form character. This drama-based learning model has been found with learning stages through the planning, implementation, and evaluation stages. At the planning stage, the teacher prepares a drama script themeonut daily life events related to mathematical topics and character value competencies to be developed. At the implementation stage, students role-play according to the theme of the drama script. As for the evaluation stage, the teacher conducts assessments during learning or student activities.